Wet-steam turbines for nuclear power plants - Leĭzerovich, A. Sh (PennWell Corp., 2005)
Annotation As traditional fossil fuels are depleted and world demand for power increases, nuclear-generated electricity has a strong future. This volume by a world-renowned scientist should be a must-read for all nuclear power plant personnel. With the widespread deployment of wet-steam turbines at nuclear power plants worldwide, readily available information on operations and maintenance is a critical factor. Wet-Steam Turbines for Nuclear Power Plants presents in-depth information essential for plant operators and managers. This book explains in clear, but detailed language, the design process by the world's leading wet-steam turbine manufacturers. It also gives readers comprehensive instruction on the subtleties of operation and maintenance of these complex components.
Keywords: Boiling water reactors -- Equipment and supplies.; Steam-turbines.; elektronické knihy; electronic books